Leakage of emerging clinically relevant multidrug-resistant Salmonella clones from pig farms - Patricia Antunes (2011)
Objectives: To assess the presence of multidrug-resistant (MDR) Salmonella with human clinical relevance in pig farms from different regions of Portugal and to analyse their mobile genetic elements associated with antibiotic resistance. Methods: Seventy-nine samples were collected from six piggeries and analysed for the presence of Salmonella. All isolates were examined for susceptibility to antimicrobial agents and representative isolates for resistance genes and class 1 integrons (PCR/restriction fragment length polymorphism). Clonality was determined by PFGE and multilocus sequence typing (MLST). Plasmid analysis included determination of size, content and characterization of the incompatibility group (rep-PCR and I-CeuI/S1-hybridization). Results: Sixty Salmonella isolates were recovered from five samples (two manure, two waste lagoons and one animal feed) in half of the piggeries studied. All isolates were resistant to at least one antibiotic (tetracycline) and 97% to at least four antibiotics from different families. In 10 isolates representing different serogroup and resistance phenotype combinations a diversity of resistance genes and integrons was detected. These isolates belonged to the internationally widespread Salmonella Rissen (ST469) and Salmonella Typhimurium DT104 (ST19) clones, as well as to the emerging Salmonella Typhimurium monophasic variant with examples of Spanish (carrying a sul3-atypical integron within IncA/C plasmids, here assigned to ST19) and European (ASSuT phenotype, assigned to ST34) clones. Conclusions: This is one of the few studies reporting emerging MDR Salmonella clones and the first one detecting Salmonella Typhimurium monophasic variant in the pig production setting. The survival of these strains in manure and waste lagoons is of concern, since these environments might allow spread of MDR bacteria beyond pig farms' boundaries.